2019
DOI: 10.3390/nu11092083
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Complications in Home Parenteral Nutrition: A Systematic Review and Meta-Analysis Comparing Peripherally-Inserted Central Catheters with Other Central Catheters

Abstract: Background: Home parenteral nutrition (HPN) has become a common therapy. There is still controversy regarding the possibility that peripherally inserted central catheters (PICCs) may diminish catheter-related blood stream infection (CRBSI) rates. Methods: We searched the PubMed database for studies reporting the rates of CRBSI with HPN. Study selection was performed independently by three investigators. Disagreements were discussed and resolved by consensus or by arbitration by an author not involved in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
1
11
0
2
Order By: Relevance
“…While similar percentages were found in other studies, the rates were higher with 1.06–5.06 events per 1,000 catheter-days [21, 27, 29]. According to a recent meta-analysis of prospective trials, the current evidence is insufficient to show differences in infection rates between tunnelled catheters and peripherally inserted central catheters while the latter shows lower infection rates compared to port systems [30]. Furthermore, there were no differences in the rates of mechanical complications and catheter-related thrombosis.…”
Section: Discussion/conclusionmentioning
confidence: 50%
“…While similar percentages were found in other studies, the rates were higher with 1.06–5.06 events per 1,000 catheter-days [21, 27, 29]. According to a recent meta-analysis of prospective trials, the current evidence is insufficient to show differences in infection rates between tunnelled catheters and peripherally inserted central catheters while the latter shows lower infection rates compared to port systems [30]. Furthermore, there were no differences in the rates of mechanical complications and catheter-related thrombosis.…”
Section: Discussion/conclusionmentioning
confidence: 50%
“…However, PICCs were usually inserted when the patient was not able to care for the VAD or when affected by an acute condition. Conversely, 1 prospective study and a meta‐analysis showed that patients using ports for HPN had a significant increase in CRBSIs compared with PICCs, whereas no difference between PICCs and tunneled‐cuffed catheters was found 38,39 …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, 1 prospective study and a meta-analysis showed that patients using ports for HPN had a significant increase in CRBSIs compared with PICCs, whereas no difference between PICCs and tunneled-cuffed catheters was found. 38,39 Nowadays, whether the PICC is an appropriate VAD for long-term treatment is still a controversial issue. The ASPEN guidelines have stated that the maximum dwell time of PICCs is unknown and that they are suitable for mediumterm PN.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that it is easy to cause catheter blockage, infection, mechanical phlebitis and other adverse complications due to improper care, of which the most serious one is catheter-related bloodstream infection (CRBSI) [5]. Previous studies [6,7] have reported that the incidence of CRBSI in NICU varied from 7.25 to 13.78%. CRBSI not only prolongs the hospitalization time of newborns, but also may increase the mortality of newborns [8].…”
Section: Introductionmentioning
confidence: 99%